2002
DOI: 10.1084/jem.20011565
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cells Are Required for the Formation of Ectopic Germinal Centers in Rheumatoid Synovitis

Abstract: The assembly of inflammatory lesions in rheumatoid arthritis is highly regulated and typically leads to the formation of lymphoid follicles with germinal center (GC) reactions. We used microdissection of such extranodal follicles to analyze the colonizing T cells. Although the repertoire of follicular T cells was diverse, a subset of T cell receptor (TCR) sequences was detected in multiple independent follicles and not in interfollicular zones, suggesting recognition of a common antigen. Unexpectedly, the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
139
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 38 publications
5
139
0
2
Order By: Relevance
“…One example of CD8 T cell influence on humoral immunity is the observation that these cells are necessary for the regulatory effects of steroid hormones on antibody secretion by B cells in female macaques [39]. Yet another example is the finding that CD8 T cells are required for the formation of ectopic GC in rheumatoid synovitis [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of CD8 T cell influence on humoral immunity is the observation that these cells are necessary for the regulatory effects of steroid hormones on antibody secretion by B cells in female macaques [39]. Yet another example is the finding that CD8 T cells are required for the formation of ectopic GC in rheumatoid synovitis [40].…”
Section: Discussionmentioning
confidence: 99%
“…One example of CD8 T cell influence on humoral immunity is the observation that these cells are necessary for the regulatory effects of steroid hormones on antibody secretion by B cells in female macaques [39]. Yet another example is the finding that CD8 T cells are required for the formation of ectopic GC in rheumatoid synovitis [40].Co-stimulatory receptors are important regulators of both cellular and humoral arms of the immune system. Freshly isolated tonsil CXCR5 + CD8 T cells express CD27 and CD28, but do not express detectable levels of other co-stimulatory molecules with relevance for B cell function such as CD70, OX40 and ICOS.…”
mentioning
confidence: 99%
“…Recently, it has been shown that about 25% of the RA tissues contain cellular infiltrates that have formed organized structures highly similar to the structures observed in lymph nodes, comprising follicular dendritic cells, T-and B-cell areas with germinal center formation. 8,15 Interestingly, several genes important for normal lymph node development were expressed in the RA-I tissues. In general, the RA-I tissues showed a high degree of T-and B-cell activation, with additional expression of genes indispensable for lymph node development (Figure 2a and b, and Table 3) that is, DOCK2 16 and B lymphocyte stimulator (BlyS, TNFSF13b).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially interesting in light of the recent unexpected observation that CD8+ T cells are required to maintain lymphoid structures with germinal centers in RA tissue transplants in SCID mice. 15 Adhesion molecules are also important in lymph node development, in particular L-selectin, 19 which is also overexpressed in the RA-Ia group. In general, the RA-Ia group was the most extreme and showed the most homogeneous expression of these genes among patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, newly defined genetic risk factors, such as CLTA-4 and PTPN22, are concerned with T cell physiology (9,10). Experiments in rheumatoid synovium/SCID mouse chimera animal models showed that synovial inflammation is strictly T cell dependent (11). Moreover, many patients show evidence of lymphoid neogenesis in the synovium, which optimizes the recognition of Ag by B and T cells (2,12).…”
Section: Unchecked Cd70 Expression On T Cells Lowers Threshold For T mentioning
confidence: 99%